2004
DOI: 10.4102/jsava.v75i1.452
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites in the intestinal tract of indigenous poultry in parts of Kenya : short communication

Abstract: A study was carried out on 456 indigenous poultry intestinal specimens from various towns in Kenya to determine the occurrence and distribution of helminth parasites in the intestinal tract of the birds. Of the specimens examined, 414 had parasites whereas the remaining 42 had none, which is an infection rate of 90.78 %. The main species of helminths found in the intestines were Raillietina sp. (47.53 %), Heterakis gallinarum (21.33 %), Ascaridia galli (10.03 %), Strongyloides avium (9.96 %), Choanotaenia infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
5
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 2 publications
6
14
5
1
Order By: Relevance
“…Even though coproscopic examination is less sensitive to diagnose than adult worms count, high prevalence of parasite was observed, which indicates that GIT parasites were a problem in the study area and there was no experience of providing prophylactic measure to control helminths. Similar findings of A. galli and H. gallinarum followed by cestode spp were recorded by (Permin et al, 1997;Birhanu Mekibib et al, 2014), but high cestode spp followed by nematodes recovered by Irungu et al, (2004). Only A. galli spp and different cestode spp have been identified in semi-intensive management system at Debre Zeit agricultural research center by (Yacob Hailu and Hagos Ashenafi, 2013).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Even though coproscopic examination is less sensitive to diagnose than adult worms count, high prevalence of parasite was observed, which indicates that GIT parasites were a problem in the study area and there was no experience of providing prophylactic measure to control helminths. Similar findings of A. galli and H. gallinarum followed by cestode spp were recorded by (Permin et al, 1997;Birhanu Mekibib et al, 2014), but high cestode spp followed by nematodes recovered by Irungu et al, (2004). Only A. galli spp and different cestode spp have been identified in semi-intensive management system at Debre Zeit agricultural research center by (Yacob Hailu and Hagos Ashenafi, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…The finding of the present study is higher than 33.5% reported by (Irungu et al, 2004) in South Eastern Kenya. The difference in prevalence might be due to management and agro-climatic variation in the two study areas.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Moreover, it has been reported that parasitic infections or their concurrent infections result in immunosuppression, especially in response to vaccines against some poultry diseases (Anne, 2006). Studies in some countries have shown that the prevalence of parasitic infestations in village chicken flocks is very high ranging from 50 to close to 100% (Irungu et al, 2004, Mungube et al, 2008, Nnadi and George, 2010, and in most cases individual birds habour more than one parasite type (Thrusfield, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…reported the prevalence of 2% in Ghana, Irungu et al 16 1.04% in Kenya and Magwisha et al 29 found 7% prevalence in adult chickens in Tanzania. Güçlü 25 found T. tenuis as 1% in Ankara.…”
mentioning
confidence: 99%